Terras Indígenas ou recursos naturais para o capital? o papel do Estado nos conflitos territoriais no Alto Xingu - Souza, Elierson Fernando de (Universidade Federal de São Carlos, 2021)
This paper aims to analyze the role of the Brazilian State in territorial conflicts in the Xingu basin. To do so, we will make a geographic cut focusing on the Alto Xingu region, state of Mato Grosso, to present the problems present in this region that generate conflicts between the peoples of the Xingu Indigenous Park and the Soybean-producing Landowners. By using the epistemological basis of David Harvey's theory on the production of capitalist space in the 21st century, which, therefore, is a theoretical framework aimed at critical analysis on the process of capitalist territorialization in globalization, we will have a work related to political geography, reason why the territory will be the main category of geographic analysis applied to the study in question.
Indigenous lands or natural resources for capital: the hole of State in the territorial conflicts in high Xingu
Keywords: Xingu; Latifúndio; Fronteira agrícola; Terras indígenas; Território; Xingu; Latifundium; Agricultural frontier; Indigenous lands; Territory.; CIENCIAS HUMANAS::GEOGRAFIA